Socio-demographic Characteristics of Pelvic Inflammatory Diseases Patients attended at a Tertiary Care Hospital in Dhaka City - Khan, Nadira; Rahman, Firoza; Jahan, Nilufar; Hafez, Fahmida; Akter, Shimul; Mohammad, Nur; Khatun, Rahela (Bangladesh Journal of Infectious Diseases, 2019)
Background: Pelvic Inflammatory disease is a very common gynaecological condition among the women. Objectives: The purpose of the present study was to see the socio-demographic characteristics of pelvic inflammatory diseases patients. Methodology: This cross-sectional study was carried out in the Department of Obstetrics and Gynaecology at Dhaka Medical College Hospital, Dhaka, Bangladesh from November 2001 to April 2002 during the period of six (06) months and December 2002 to February 2003 for three (03) months with the total duration of nine (09) months. Women at any age who were suffering from chronic pelvic inflammatory disease (PID) attended at the OPD of gynecology Department at Dhaka Medical College Hospital, Dhaka, Bangladesh were selected as study population. Detailed history of each patient was taken and thorough physical examination was performed. Result: A total number of 150 cases were recruited for this study. Among 150 case of chronic pelvic inflammatory disease (PID) majority of the patients (54%) belonged to the age group of 26 to 35 years of age group. Majority of the patients were married (90.7%). Among 150 cases 80.0% patients were house wife. Regarding husbands’ occupation, 13.3% cases were businessman. Illiterate was in 44.7% cases. Among all patients 48.0% cases were found to be from lower socioeconomic status. Majority of the patients were from urban area (78.7% cases). Conclusion: In conclusion young reproductive age married illiterate women with low socio0-economic condition are the mostly suffering from pelvic inflammatory diseases Bangladesh Journal of Infectious Diseases, December 2018; 5(2): 41-44